2007
DOI: 10.1136/jnnp.2006.094342
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotics and cognitive decline in Alzheimer's disease: the LASER-Alzheimer's disease longitudinal study

Abstract: Objective: To investigate in a longitudinal cohort of people with Alzheimer's disease whether taking antipsychotics is associated with more rapid cognitive deterioration. Method: From a sample of 224 people with Alzheimer's disease recruited as epidemiologically representative, those taking antipsychotic drugs for more than 6 months were compared with those who were not, in terms of change in three measures of cognition. The effects of potential mediators and confounders (demographic factors, neuropsychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…We did not examine the duration of illness prior to assessment as this has not been found to be a determinant of survival time when age and disease severity are taken into account, but would expect that duration of illness would be related to severity of cognitive impairment (Walsh et al, 1990;Heyman et al, 1996;Moritz et al, 1997;Larson et al, 2004). Survival was not associated with the prescription of antipsychotic or antidepresssant medication, in agreement with our previous study using the same cohort which found that antipsychotic medication was not associated with cognitive decline or survival (Livingston et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We did not examine the duration of illness prior to assessment as this has not been found to be a determinant of survival time when age and disease severity are taken into account, but would expect that duration of illness would be related to severity of cognitive impairment (Walsh et al, 1990;Heyman et al, 1996;Moritz et al, 1997;Larson et al, 2004). Survival was not associated with the prescription of antipsychotic or antidepresssant medication, in agreement with our previous study using the same cohort which found that antipsychotic medication was not associated with cognitive decline or survival (Livingston et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…The derivation cohort was 224 people recruited as part of a naturalistic, longitudinal study of people with AD, covering the London and the South East Region (LASER-AD study) (Livingston et al, 2007). Local research ethics committees approved the study.…”
Section: Derivation Cohortmentioning
confidence: 99%
“…More than 80% of those without any of these risk factors survived at least three and a half years, while only around a third of those with three risk factors survived this long. Survival was not associated with the prescription of antipsychotic or antidepressant medication, in agreement with Livingston et al, (2007) who found that antipsychotic medication was not associated with cognitive decline or survival. There is a clear difference in the survival time of people with mild or moderate AD according to their possession of the identified risk-factors.…”
Section: Predictors Of Institutionalisation In Alzheimer's Diseasesupporting
confidence: 88%
“…The areas examined in this cohort of 224 people with AD and their carers include disease detection ; predictors of progression (Fox et al, 2011;Livingston et al, 2007;Regan, et al, 2006), institutionalisation (Habermann et al, 2009) and mortality in AD (Paradise et al, 2009); costing models for AD , Rive et al, 2010aRive et al, 2010b); symptoms of AD (Train et al, 2004;Regan et al, 2005;Ryu et al, 2005) and characteristics of moderate-severe AD ; quality of life (Hoe et al, 2005;Hoe et al, 2007) and ageing well in adversity (Livingston et al, 2008). The issues affecting carers of people with AD, include psychological morbidity Maidment et al, 2005), attachment (Cooper et al, 2008a), coping Cooper et al, 2008b;Cooper et al, 2008c), safety in AD (Walker et al, 2006), carer attributions of behaviour in AD (Paton et al, 2004) and elder abuse in AD (Cooper et al, 2008d).…”
Section: Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation